Perspectives of dementia from Asian communities living in New Zealand: A focus group of Asian health care professionals. (14th August 2019) - Cheung, Gary; Appleton, Kerry; Boyd, Michal; Cullum, Sarah
Abstract : Objective: The number of Asian New Zealanders with dementia is growing. The objective of this study was to explore with a group of Asian health care professionals about public attitudes towards dementia in Asian communities in New Zealand, the stigma of dementia, and how best to develop culturally appropriate services for Asian people and families living with dementia. Methods: A focus group was conducted with a group of bilingual Asian health care professionals. A topic guide was developed based on the discussion at a prior meeting with the Cross Cultural Interest Group. The data were independently analysed by three researchers using the thematic qualitative methodology. Results: Eleven overseas‐born Asian health care professionals (Chinese: n = 9, 82%) participated in the focus group. Four main themes emerged from the data: (a) cultural interpretations of dementia; (b) stigma; (c) filial piety; and (d) inequity in the availability of resources. Conclusion: Our findings suggest that much work is needed to destigmatise dementia in New Zealand Asian communities, through psychoeducation, public awareness, and the availability of readily accessible services that can meet their cultural and language needs.